B cells are critical to t-cell–mediated antitumor immunity induced by a combined immune-stimulatory/ conditionally cytotoxic therapy for glioblastoma - Candolfi, Marianela (2011)
We have demonstrated that modifying the tumor microenvironment through intratumoral administration of adenoviral vectors (Ad) encoding the conditional cytotoxic molecule, i.e., HSV1-TK and the immune-stimulatory cytokine, i.e., fms-like tyrosine kinase 3 ligand (Flt3L) leads to T-cell-dependent tumor regression in rodent models of glioblastoma. We investigated the role of B cells during immune-mediated glioblastoma multiforme regression. Although treatment with Ad-TK+Ad-Flt3L induced tumor regression in 60% of wild-type (WT) mice, it completely failed in B-cell-deficient Igh6-/- mice. Tumor-specific T-cell precursors were detected in Ad-TK+Ad-Flt3L-treated WT mice but not in Igh6-/- mice. The treatment also failed in WT mice depleted of total B cells or marginal zone B cells. Because we could not detect circulating antibodies against tumor cells and the treatment was equally efficient in WT mice and in mice with B-cell-specific deletion of Prdm 1 (encoding Blimp-1), in which B cells are present but unable to fully differentiate into antibody-secreting plasma cells, tumor regression in this model is not dependent on B cells’ production of tumor antigen-specific immunoglobulins. Instead, B cells seem to play a role as antigen-presenting cells (APCs). Treatment with Ad-TK+Ad-Flt3L led to an increase in the number of B cells in the cervical lymph nodes, which stimulated the proliferation of syngeneic T cells and induced clonal expansion of antitumor T cells. Our data show that B cells act as APCs, playing a critical role in clonal expansion of tumor antigen-specific T cells and brain tumor regression.